Theory of femtosecond coherent double-pump single-molecule spectroscopy : application to light harvesting complexes - Chen, Lipeng (2015)
We develop a first principles theoretical description of femtosecond double-pump single-molecule signals of molecular aggregates. We incorporate all singly-excited electronic states and vibrational modes with significant electron-vibrational coupling into a system Hamiltonian and treat the ensuing system dynamics within the Davydov D1 Ansatz. The remaining intra- and inter-molecular vibrational modes are treated as a heat bath and their effect is accounted for through lineshape functions. We apply our theory to simulate single-molecule signals of the light harvesting complex II. The calculated signals exhibit pronounced oscillations of mixed electron-vibrational (vibronic) origin. Their period decreases with decreasing electron-vibrational couplings.